An overall safety concept for nuclear power plants. (1st December 2022) - Hyvärinen, Juhani; Vihavainen, Juhani; Ylönen, Marja; Valkonen, Janne
Highlights: Paper extends the defence-in-depth (DiD) thinking to the organizational context. The ORSAC framework is a matrix of safety functions overlaying the DiD lines. The ORSAC is a powerful tool depicting the whole plant as a system of systems. The ORSAC framework is applied to large LWR and SMRs. The number of independent DiD lines is much smaller than in theory. Abstract: A comprehensive understanding of the "safety" of nuclear reactors is essential for effective and efficient safety management by licensees and regulation by authorities. Nuclear reactors are designed subject to incomplete knowledge of factors that affect their safety. The idea of defence-in-depth has evolved to combat the threat of the unknown; it is implemented by means of technical artefacts, leading to a complex set of technical safety requirements to prevent accidental radioactive releases. Nuclear power plants have thus become systems of technical systems . Similarly, significant human and organizational aspects are involved in nuclear power plant construction and operation; a nuclear power plant is an organization of organizations. Earlier studies have identified the need for holistic understanding of safety and accounting for the technical and organizational aspects simultaneously (Harvey and Stanton, 2014). This paper seeks to clarify the concept of defence-in-depth using the Overall Safety Concept (ORSAC) developed at LUT (Hyvärinen et al., 2016), and the sociotechnical systems view in the nuclear power industry context, extending defence-in-depth thinking to the organizational context in one transparent framework. We show how organizational and technical aspects affect each other in the operation of nuclear power plants. This paper paves the way for systematic modelling of how technical and organizational aspects affect each other.